PERAN ORANG TUA TERHADAP ANAK DALAM PROGRAM BELAJAR DARI RUMAH DI MASA PANDEMI COVID-19 - Inom Nasution; Suharian Suharian (Jurnal Visipena, 2020)
This study used a qualitative narrative inquiry design. This study aims to explore the experience of the role of parents in the education of children at home during the Covid 19 period. Participants were chosen by one parent because they were willing to participate in telling their experiences in educating children at home during the Covid 19 period. Demographic information from parents in South Aceh. The method used is the interview procedure. Individual interviews were conducted with casual storytelling conducted in participant's house by recording audio during the conversation. The data obtained from the interviews were analyzed thematically. Triangulation uses transcripts, data sources, information data collection, and field notes. This study found the role of parents in family education for children during the Covid-19 period, including: Children must be controlled so they do not leave the house during the COVID-19 pandemic; Ensure that children's food and nutritional needs are met during the COVID-19 pandemic; and Educating and guiding them in doing assignments and replacing the role of teachers in school. Parents fulfill the needs of spiritual understanding, supervision and motivation as well as learning facility providers in assisting children in overcoming all learning difficulties. The main educational material emphasizes the religious aspect by inviting children to pray, recite the Qur'an, memorize daily prayers and religious materials. Provides understanding of knowledge, forming personalities to be sensitive to the environment. Barriers to informal education or family timing. Abstrak Peneltian ini menggunakan design kualitatif narrative inquiry. Penelitian ini bertujuan untuk menggali pengalaman peran orang tua dalam pendidikan anak di rumah masa covid 19. Participant dipilih satu orang tua karena bersedia berpartisipasi menceritakan pengalamannya dalam dalam pendidikan anak di rumah masa covid 19. Informasi demografis dari orang tua di Aceh selatan. Metode yang digunakan dengan prosedur wawancara. Wawancara individu dilakukan dengan bercerita santai dilakukan di rumah participant dengan cara merekam audio selama percakapan. Data yang diperoleh dari hasil wawancara dianalisis secara tematik. Triangulasi menggunakan transkrip, sumber data, pengumpulan data informasi, dan catatan lapangan. Penelitian ini menemukan peran orang tua dalam pendidikan keluarga pada anak masa covid-19 diantaranya: Anak harus dikontrol agar tidak keluar rumah selama pandemi covid 19; Memastikan bahwa kebutuhan makan dan gizi anak terpenuhi selama pandemi covid 19; dan Mendidik dan membimbing mereka dalam mengerjakan tugas-tugas dan menggantikan peran guru disekolah. Orang tua memenuhi kebutuhan pemahaman spiritual, pengawasan dan motivasi serta penyedia fasilitas belajar dalam mendampingi anak dalam mengatasi kesulitan semua pembelajaran. Materi pendidikan utama menekankan pada aspek agama dengan mengajak anak untuk sholat, mengaji, menghafal doa harian dan materi keagamaan. Memberi pemahaman ilmu, membentuk kepribadian agar peka terhadap lingkungan. Hambatan dalam pendidikan informal atau keluarga pengaturan waktu.